2017
DOI: 10.1128/jcm.00152-17
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tuberculosis Patient Mortality Associated with Mycobacterium tuberculosis Mutations Conferring Resistance to Second-Line Antituberculous Drugs

Abstract: Rapid molecular diagnostics have great potential to limit the spread of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) (M/XDR-TB). These technologies detect mutations in the genome that confer phenotypic drug resistance. However, there have been few data published regarding the relationships between the detected resistance mutations and M/XDR-TB treatment outcomes, limiting our current ability to exploit the full potential of molecular diagnostics. We analyzed cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Unfortunately, development of drug resistance in the form of monoresistant-TB or MDR-/XDR-/TDR-TB critically obstructs the efficacy of currently available drug regimens. Improper use of antibiotics, lack of treatment adherence, mutational modifications, and limited access to drugs or diagnostic tools all are risk factors associated with the emergence of resistant forms of TB (Lange et al, 2014 ; Georghiou et al, 2017 ; Manson et al, 2017 ). Besides, acquired drug-resistant TB and transmitted drug-resistant TB pose a serious threat to global TB control and population health.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, development of drug resistance in the form of monoresistant-TB or MDR-/XDR-/TDR-TB critically obstructs the efficacy of currently available drug regimens. Improper use of antibiotics, lack of treatment adherence, mutational modifications, and limited access to drugs or diagnostic tools all are risk factors associated with the emergence of resistant forms of TB (Lange et al, 2014 ; Georghiou et al, 2017 ; Manson et al, 2017 ). Besides, acquired drug-resistant TB and transmitted drug-resistant TB pose a serious threat to global TB control and population health.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the moderate-level resistance mediated by gyrA gene mutation did not show a significant statistical effect [ 34 ]. A multinational cohort study also suggested the role of high-level resistance-related gyrA mutations increased the risk of death for MDR/XDR-TB patients [ 35 ]. High doses of Mfx added to the MDR-TB treatment regimen can prevent patients from developing XDR-TB, indicating that low concentrations of FQ resistance caused by mutations in the gyrA locus can be treated with high doses of Mfx [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resistance genotype [ 49 , 50 , 51 ] determines the resistance phenotype. Take the evolutionary history of Mycobacterium tuberculosis resistance to second-line anti-tuberculous as a scholarly medical genetic example to illustrate the simple Mendelian genotype–phenotype relations [ 52 , 53 , 54 , 55 ].…”
Section: Multidrug Resistance: Updated Terms and Definitionsmentioning
confidence: 99%
“…The higher level of organization is the antibiotics resistance cassette [ 62 , 63 , 64 ]. The respective resistance gene(s) could be localized either on the chromosome [ 51 ], or in a plasmid [ 65 , 66 , 67 , 68 , 69 ], either as non-conjugative [ 62 ], conjugative [ 70 , 71 ], or in an episome [ 72 ].…”
Section: Multidrug Resistance: Updated Terms and Definitionsmentioning
confidence: 99%